Double-Wavelength-Switchable Molecular Self-Assembly of a Photoacid and Spirooxazine in an Aqueous Solution - Zika, Alexander; Agarwal, Mohit; Schweins, Ralf; Gröhn, Franziska (Journal of Physical Chemistry Letters, 2023)
Quadruple-switchable nanoscale assemblies are built by combining two types of water-soluble molecular photoswitches through dipole-dipole interaction. Uniting the wavelength-specific proton dissociation of a photoacid and ring-opening of an anionic spirooxazine results in an assembly that can be addressed by irradiation with two different wavelengths: pH and darkness.
CRIS-Team Scopus Importer:2023-11-17